"The Land is Mine": Elias Khoury Writes Back to Leon Uris†. Issue 4 (19th May 2019) - AlJahdali, Samar H.
Abstract : This essay explores the architecture of erasure, physical and discursive, in literary representations of Palestine. Elias Khoury's Gate of the Sun (1998; trans. 2005) is read contrapuntally with Leon Uris's The Haj (1984), with particular focus on the politics and poetics of settler narrative and counter-narrative. The study argues the case of Palestine problematizes the settler colonial paradigm as theorized by Patrick Wolfe and Lorenzo Veracini. Hence, the focus, here, on a Jewish American novel instead of Israeli narratives serves to suggest that the Zionist settler enterprise is inseparable from US imperialism, and therefore challenges conceptualizations of a purely settler phenomenon in Palestine.